Creating Harmonious Relationships in the Classroom Through the Teacher's Positive Personality - Marsita, Nurfaiza; Akmal, Fauzi; Ringgit, Awang (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
Being a teacher is not an easy job. One of the things that a teacher needs to do is to be able to build a positive relationship between teachers and students. This is the purpose of this study, which is to find out how to build a better relationship and respond appropriately in order to create a positive relationship between teachers and students. The data for this study was sourced from books and electronic scientific articles. The data collection technique used was content analysis, with the aim of helping teachers build good or positive relationships and establish a good image of teachers in the student environment. In addition, it serves as a consideration in measuring how to behave and how to respond to students so that a positive relationship between teachers and students can be established.